Workshops for the development of evidence-based practice among nursing leaders: a pilot study - Camargo, Fernanda Carolina (2017)
The objective of this study was to analyze the effectiveness of motivational workshops to implement Evidence Based Practice (EBP) among nursing leaders. This was a pilot, virtually experimental, before and after type study, conducted in a public teaching hospital. Researchers applied the Evidence-Based Practice Questionnaire and The Barriers to Research Utilization Scale and analyzed differences of means via Student’s t-test for paired samples or Wilcoxon’s test for non-parametric data. Although they had positive attitudes towards EBP, the workshops were not effective in broadening skills (initial mean=109.8; final mean=107, p=0.58). However, they significantly reduced the perception of barriers (initial mean=73.2; final mean=66.6, p<0.10), the main ones being related to the lack of authority to propose changes, and work overload. Researchers observed that the intervention was effective for motivational purposes. Conducting new research to assess the inclusion of this practice in units headed by nursing leaders is encouraged.